Real-world use of PCSK9 inhibitors: A single-center experience. Issue 1 (January 2019) - Sarsam, Sinan; Berry, Abeer; Degheim, George; Singh, Robby; Zughaib, Marcel
Objective: Hyperlipidemia is an important risk factor for atherosclerotic cardiovascular disease. Many patients are intolerant to or have limited benefit from statins. Proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors have been approved for treating hyperlipidemia in these patients. We sought to investigate the impact of these medications in a real-world cardiology practice. Methods: This was a retrospective study of 17 patients with either heterozygous familial hypercholesterolemia or established atherosclerotic cardiovascular disease with low-density lipoprotein cholesterol (LDL-C) levels above the treatment target despite maximally tolerated statins. Baseline lipid profile was compared with a repeat lipid profile obtained 4 to 6 weeks after initiating treatment with a PCSK9 inhibitor. Results: The average duration of PCSK9 inhibitor treatment was 10.7 months. Lipid profile comparison showed that total cholesterol decreased from 243 ± 72 to 148 ± 39 (mg/dL) (39% reduction), triglycerides decreased from 185 ± 86 to 149 ± 62 (mg/dL) (19.5% reduction), high-density lipoprotein cholesterol increased from 56 ± 20 to 62 ± 26 (mg/dL) (10.7% increase), and LDL-C decreased from 154 ± 30 to 57 ± 32 (mg/dL) (63% reduction) from baseline. Conclusions: PCSK9 inhibitors as add-on therapy to maximally tolerated statins resulted in an approximately 63% reduction in LDL-C.